The First Fifty Years of the General Hospital of Majorca: From its Foundation Until the Promulgation of its Ordinances (1456-1514) - Cassanyes Roig, Albert (En la España Medieval, 2018)
This paper analyses the initial period of the establishing of the General Hospital of Majorca, from its founding in 1456 until the promulgation of its ordinances in 1514. To reach this purpose, the paper uses some sources that have not been worked systematically by the previous researches, although they are known, but we also provide some unpublished documents. The General Hospital of Majorca was the result of the union of the pre-existing small hospitals. This procedure was not new, but it was used in the Crown of Aragon from the founding of the Hospital of the Saint Cross of Barcelona in 1401. The municipal authorities seize the control of the hospital institution, while the Church had a secondary role in the administrative functions. During its first years, the General Hospital must seek to necessary sources of income to exercise its hospital functions and construct an appropriate building to attend to poor people and foundling children. The Ordinances of 1514 supposed that the institution provided itself with its first regulation. Therefore, the founding of the General Hospital of Majorca has to be framed in the process of unification of hospitals and of laicization of the assistance, both characteristic of the mid-fifteenth century.
Keywords: assistance; General Hospital; Majorca; foundling children; ordinances.